Copper Nanoparticles and Reduced Graphene Oxide as an Electrode Modifier for the Development of an Electrochemical Sensing Platform for Chloroquine Phosphate Determination - Barreto, Francisco Contini [UNESP]; da Silva, Martin Kássio Leme [UNESP]; Cesarino, Ivana [UNESP] (MDPI, 2023)
This study describes the use of copper nanoparticles (CuNPs) and reduced graphene oxide (rGO) as an electrode modifier for the determination of chloroquine phosphate (CQP). The synthetized rGO-CuNPs composite was morphologically characterized using scanning electron microscopy and electrochemically characterized using cyclic voltammetry. The parameters were optimized and the developed electrochemical sensor was applied in the determination of CQP using square-wave voltammetry (SWV). The analytical range for the determination of CQP was 0.5 to 110 μmol L−1 (one of the highest linear ranges for CQP considering electrochemical sensors), with limits of detection and quantification of 0.23 and 0.78 μmol L−1, respectively. Finally, the glassy carbon (GC) electrode modified with rGO-CuNPs was used for quantification of CQP in tap water; a study was carried out with interferents using SWV and obtained great results. The use of rGO-CuNP material as an electrode modifier was thus shown to be a good alternative for the development of low-cost devices for CQP analysis.
Keywords: antimalarial drug; chloroquine phosphate; copper nanoparticles; electrochemical sensor; reduced graphene oxide